Evaluation of time, attendance of medical staff, and resources during stereotactic radiotherapy/radiosurgery - Zabel-du Bois, Angelika; Milker-Zabel, Stefanie; Debus, Jürgen (Strahlentherapie und Onkologie, 2012)
BackgroundThe German Society of Radiation Oncology (“Deutsche Gesellschaft für Radioonkologie”, DEGRO) initiated a multicenter trial to develop and evaluate adequate modules to assert core processes and subprocesses in radiotherapy. The aim of this prospective evaluation was to methodical assess the required resources (technical equipment and medical staff) for stereotactic radiotherapy/radiosurgery.Material and methodsAt two radiotherapy centers of excellence (University Hospitals of Heidelberg and Marburg/Gießen), the manpower and time required for the implementation of intra- and extracranial stereotactic radiotherapy was prospectively collected consistently over a 3-month period. The data were collected using specifically developed process acquisition tools and standard forms and were evaluated using specific process analysis tools.ResultsFor intracranial (extracranial) fractionated stereotactic radiotherapy (FSRT) and radiosurgery (RS), a total of 1,925 (270) and 199 (36) records, respectively, could be evaluated. The approximate time needed to customize the immobilization device was median 37 min (89 min) for FRST and 31 min (26 min) for RS, for the contrast enhanced planning studies 22 and 27 min (25 and 28 min), for physical treatment planning 122 and 59 min (187 and 27 min), for the first and routine radiotherapy sessions for FSRT 40 and 13 min (58 and 31 min), respectively. The median time needed for the RS session was 58 min (45 min). The corresponding minimal manpower needed was 2 technicians for customization of the immobilization device, 2.5 technicians and 1 consultant for the contrast-enhanced planning studies, 1 consultant, 0.5 resident and 0.67 medical physics expert (MPE) for physical treatment planning, as well as 1 consultant, 0.5 resident, and 2.5 technicians for the first radiotherapy treatment and 2.33 technicians for routine radiotherapy sessions.ConclusionFor the first time, the resource requirements for a radiotherapy department for the maintenance, protection and optimization of operational readiness for the application of intra- and extracranial stereotactic radiotherapy was determined methodically.